Analisis Risiko Politik dan Keamanan PT Freeport Indonesia sebagai Dampak dari Kebijakan Calon Presiden dan Wakil Presiden Pemilu 2024 [Analysis on the Political and Security Risks of PT Freeport Indonesia as the Impact of the Policy of the 2024 General Election Candidacy] - Putri, Sisilia; Pandjaitan XIV, Qanszelir GB (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2023)
The visions and missions of each presidential and vice-presidential candidate pair in the 2024 elections have the potential to create changes in regulations, policies, and governance of the mining industry in Indonesia. These changes pose political and security risks for foreign mining industries, one of which is PT Freeport Indonesia with McMoRan investments. This study aims to explore the impact of political change on the operational stability of PT Freeport Indonesia, identify the role of government policy in addressing economic inequality, and propose more inclusive and sustainable policy alternatives. To spell out the phenomenon, the researcher used qualitative research methods with comparative analysis techniques through documentation studies. The results show there are potential political and security risks to Freeport McMoRan's operational stability in the context of cohesiveness of government, strength of within-system opposition, rule of law, and corruption. The tightening of regulations under the leadership of Anies Baswedan and Muhaimin Iskandar are projected to disrupt or change the operational conditions of PT Freeport Indonesia. Meanwhile, the leadership of Prabowo Subianto and Gibran Rakabuming Raka are not considered to have a significant impact on Freeport-McMoran. Meanwhile, the emphasis on governance regulations under the leadership of Ganjar Pranowo and Mahfud MD will inflict uncertainty for the mining industry and investment in Papua. The upcoming leadership regulations promise positive changes for development and the environment in Indonesia, but too drastic policy changes could negatively impact the mining companies and the long-term investments.Bahasa Indonesia Abstract: Visi dan misi masing-masing pasangan calon presiden dan wakil presiden pada Pemilu 2024 berpotensi melahirkan perubahan regulasi, kebijakan, dan tata kelola industri tambang di Indonesia. Perubahan tersebut menimbulkan risiko politik dan keamanan bagi industri pertambangan asing, salah satunya adalah PT Freeport Indonesia dengan investasi McMoRan. Penelitian ini bertujuan untuk mengeksplorasi dampak perubahan politik terhadap kestabilan operasional PT Freeport Indonesia, mengidentifikasi peran kebijakan pemerintah dalam mengatasi ketimpangan ekonomi, serta mengusulkan alternatif kebijakan yang lebih inklusif dan berkelanjutan. Untuk menguraikan fenomena tersebut, peneliti menggunakan metode penelitian kualitatif dengan teknis analisis komparatif melalui studi dokumentasi. Hasil penelitian menunjukkan adanya potensi risiko politik dan keamanan pada kestabilan operasional Freeport McMoRan dalam konteks cohesiveness of government, strength of within-system opposition, rule of law, dan corruption. Pengetatan regulasi pada kepemimpinan Anies Baswedan dan Muhaimin Iskandar diproyeksikan akan mengganggu atau mengubah kondisi operasional PT Freeport Indonesia. Sementara itu, kepemimpinan Prabowo Subianto dan Gibran Rakabuming Raka dinilai tidak menimbulkan dampak yang signifikan bagi Freeport - McMoran. Adapun, penekanan regulasi tata kelola pada kepemimpinan Ganjar Pranowo dan Mahfud MD akan menimbulkan ketidakpastian bagi industri tambang dan investasi di Papua. Regulasi kepemimpinan mendatang menjanjikan perubahan positif bagi pembangunan dan lingkungan di Indonesia, tetapi perubahan kebijakan yang terlalu drastis dapat berdampak negatif bagi perusahaan tambang dan investasi jangka panjang.